Two Convenient Methods for Detection of Non-Dairy Fats in Butter by Dynamic Light Scattering and Luminescence Spectroscopy - Leonid L. Chaikov; Marina N. Kirichenko; Svetlana V. Krivokhizha; Maskhud R. Kupov; Andrey N. Lobanov; Pavel P. Sverbil; Egor I. Nagaev; Alexey V. Shkirin (Applied Sciences, 2023)
We propose two convenient methods to quickly detect the presence of non-milk fat (palm oil) in butter, as well as to determine its amount in the product. For the first time, we have experimentally obtained the dependence of the size of drops of an alcoholic emulsion of oil or spread on the content of palm oil in it by the dynamic light scattering (DLS) method. We have also obtained the dependence of intensity ratio of the components of spread luminescence spectrum on palm oil content when excited at a wavelength λ = 266 nm. These results allowed us to propose two methods for determining the adulteration of butter with palm oil using DLS and measuring luminescence spectra. The two methods are physically independent but successfully supplement each other. DLS and luminescent methods for determining the proportion of palm oil give errors of no more than 10% and 6%, respectively.